The Investigation of Teachers’ and Students’ Attitudes and Enjoyment towards ChatGPT for English Language Learning - Ni Made Karina Putri Winarsa; Made Hery Santosa; Luh Indrayani (STKIP AGAMA HINDU SINGARAJA, 2025)
Previous research on ChatGPT has revealed mixed attitudes among teachers and students, highlighting the need for further investigation. While most studies focused on the university level, there is an essential gap in attitude research focusing on secondary school settings, exploring the enjoyment that affects attitudes. This study aimed to investigate teachers’ and students’ attitudes and enjoyment towards ChatGPT in English language learning. An explanatory sequential mixed-method design was employed, involving 8 English teachers and 311 students from a secondary school in Singaraja. The data in this study were collected through questionnaires and interviews. The quantitative findings showed positive attitudes among teachers and students, but based on the constituent aspects, it is shown that teachers tended to have more positive attitudes than students. Qualitative interviews further highlighted that ChatGPT contributed to emotional experiences influenced by the tool's strengths and weaknesses, as well as social perceptions of users. These findings suggested that integrating ChatGPT into English language learning stimulated positive responses due to its advantages in reducing academic burdens. However, the tool's shortcomings have also drawn attention, including triggering negative behavioral risks and overreliance among students. English educators needed to guide students in using ChatGPT more ethically by rechecking and confirming students' answers suspected to be AI-based. In addition, policymakers can initiate ChatGPT and AI training periodically to enhance teachers’ compatibility, particularly for senior teachers.